Bank Health Analysis to Measure the Financial Performance of PT Bank Rakyat Indonesia Tbk for the 2015-2024 Period - Riana, Dwi; Yuvita, Heni (Jurnal Sains Sosio Humaniora, 2025)
This study aims to assess the health level of PT Bank Rakyat Indonesia (Persero) Tbk during the period 2015–2024 using the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method. Bank health assessments are an important aspect in maintaining the stability of the banking system, increasing public trust, and supporting the sustainability of company performance. This study uses a quantitative descriptive method by utilizing secondary data obtained from the annual reports and financial statements of PT Bank Rakyat Indonesia (Persero) Tbk for the period 2015–2024. The Risk Profile aspect measurement was carried out using Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) ratios, the Good Corporate Governance aspect using GCG self-assessment results, the Earnings aspect using Net Interest Margin (NIM), while the Capital aspect used the Capital Adequacy Ratio (CAR). The results of this study show that BRI has excellent ability to manage risk, generate profits, maintain liquidity, and maintain capital adequacy so that it is able to support operational sustainability and business growth in the long term.